Haig's coup : how Richard Nixon's closest aide forced him from office - Locker, Ray (Potomac Books, an imprint of the University of Nebraska Press, 2019)
"The true story of how Chief of Staff Alexander Haig orchestrated Richard Nixon's demise, resignation, and pardon."--Provided by publisher